Enhanced extracellular production of recombinant proteins in Escherichia coli by co-expression with Bacillus cereus phospholipase C - Su, Lingqia (Microb Cell Fact, 2017)
BACKGROUND: Our laboratory has reported a strategy for improving the extracellular production of recombinant proteins through co-expression with Thermobifida fusca cutinase, which increases membrane permeability via its phospholipid hydrolysis activity. However, the foam generated by the lysophospholipid product makes the fermentation process difficult to control in a fermentor. Phospholipase C (PLC) catalyzes the hydrolysis of phospholipids to produce sn1,2-diacylglycerides and organic phosphate, which do not induce foam formation. Therefore, co-expression with Bacillus cereus PLC was investigated as a method to improve the extracellular production of recombinant proteins. RESULTS: When B. cereus PLC was expressed in Escherichia coli without its signal peptide, 95.3% of the total PLC activity was detected in the culture supernatant. PLC expression enhanced membrane permeability without obvious cell lysis. Then, six test enzymes, three secretory and three cytosolic, were co-expressed with B. cereus PLC. The enhancement of extracellular production correlated strongly with the molecular mass of the test enzyme. Extracellular production of Streptomyces sp. FA1 xylanase (43 kDa), which had the lowest molecular mass among the secretory enzymes, was 4.0-fold that of its individual expression control. Extracellular production of glutamate decarboxylase (51 kDa), which had the lowest molecular mass among the cytosolic enzymes, reached 26.7 U/mL; 88.3% of the total activity produced. This strategy was effectively scaled up using a 3-L fermentor. No obvious foam was generated during this fermentation process. CONCLUSIONS: This is the first study to detail the enhanced extracellular production of recombinant proteins through co-expression with PLC. This new strategy, which is especially appropriate for lower molecular mass proteins, allows large-scale protein production in an easily controlled fermentation process.